A literatura como traição: transgressões de cenas bíblicas - Késia Rodrigues de Oliveira (2023)
This thesis investigates how betrayal, transgression, and subversion are presented in short stories by Jorge Luis Borges, Moacyr Scliar, and Deana Barroqueiro, the motif of which is the reverse rewriting of the histories of the great biblical leaders Abraham, Moses, and David, as well as the deceitful Cain, Esau, and Judas. The revisiting of the biblical scenes in which these characters appear constitutes a way of understanding literature as betrayal. This interpretation is closely linked to the notions of rewriting, memory, appropriation, and disappropriation developed by Antoine Compagnon, Umberto Eco, Michel Schneider, Ricardo Piglia, and Harold Bloom. Based on these concepts, this study also discusses how these narratives refer to a profanation of the sacred, in the sense that they put aside the sacred character of the Scriptures, bringing to light human aspects of stories and thus pointing to the multiple possibilities of interpretations of the Bible and for the production of new texts.